PEDAGOGICAL POTENTIAL OF RESOURCE-BASED TEACHING IN PROMOTING HEALTH-PRE- SERVING EDUCATIONAL CONTEXTS - Lina Rybalko; Tetiana Hulko; Tetiana Plachynda; Anton Kovalev; Walery Zukow (Alfred Nobel University Journal of Pedagogy and Psychology)
Modernity challenges higher education institutions with the need to reform the education system, improve it, and enhance the quality and competitiveness of graduates on the European labour market. In recent years, the education system in the context of informatization has undergone significant changes in connection with the development and practical use of new information and communication technologies: the practice of electronic learning (E-learning), and resource-based learning (Resource Based Learning) is widely used in the education system in foreign and partly domestic institutions of higher education. The purpose of the article is to analyse the effectiveness of the implementation of resource-based learning in a health preserving educational environment of higher educational institutions. Research methods. The study included 493 undergraduate students (N = 493) from the National University “Yuri Kondratyuk Poltava Polytechnic” during the 2023-2024 academic year. The participants were enrolled in the Physical Education and Sports specialty program and were randomly assigned to either the experimental group (EG, n = 240) or control group (CG, n = 253). This study examines the implementation of resource-based learning (RBL) in higher education as a holistic dynamic process that optimizes the use of personnel, logistical, educational, methodological, financial, and information resources through the “student-teacher-librarian” triad. The research demonstrates how RBL, when implemented within a health-preserving educational environment, creates conditions that maintain and enhance participants’ health while facilitating effective learning. Results show significant improvements in student performance and engagement when RBL is applied with health- preserving considerations, particularly in mobile learning contexts. The approach creates a comfortable, stress-free learning environment while promoting independent cognitive activity and health-conscious behaviours. Conclusions. The study analyses the effectiveness of RBL implementation while maintaining health- preserving conditions. Our findings demonstrate that when RBL is implemented within a carefully designed health-preserving educational environment, it creates optimal conditions for learning while ensuring health maintenance and enhancement among all participants. The research, conducted at the National University “Yuri Kondratyuk Poltava Polytechnic,” revealed significant improvements in student performance and engagement metrics. Notably, the experimental group showed a 6.25% increase in very high performance levels and a complete elimination of very low performance levels, compared to minimal changes in the control group. The study finds that mobile learning, as a form of RBL, can effectively create a health- preserving educational environment while promoting independent learning and cognitive development. The results validate the effectiveness of combining RBL with health-preserving considerations in higher education, offering a model for implementing technology-enhanced learning without compromising student wellbeing.